Determining the effects of different posted speed limits on highway - Ambak, Kamarudin (2004)
Vehicles arc the important element in transportation system. It is being used for traveling on road to fulfill the demand of working, business, vacation, etc. About I .4% of registered vehicles getting involved in road crashes in Malaysia. There were found about 4. 9 deaths per I 0,000 from registered vehicles in year 2002. Statistical reports road accident (PDRM) shows that the road accident by type of faults about 15% by speeding behavior. These statistic lead to the inevitable conclusion that the impact of road cra shes due to speeding behaviour could be fatal and severed injuries. Therefore, a study on the effects of different posted speed limits to determine the operating speed and compliance of speed limits was carried out. The sites were identified and selected that located on PLUS expressway stretch from Kuala Lumpur to Scremban. The section of locations were in Sg.Bcsi area with 80 km/h posted speed limit, Serdang area 90 km/h posted speed limits and Seremban with 1 IO km/h posted speed limits. There were I 00 data collected in spot speed study was carried out for each vehicles c!assification namely motorcycle, car, taxi, light van and utility, medium lorry, heavy lorry and bus. The collection of data were taken from 10.00 a.m to 1.00 p.m within a month and covered for both southbound and northbound direction. The vehicles that traveling at or below posted or commercial speed limits was classified as complied with the speed limits, those who traveling above posted or commercial speed limits at all was classified as not complied with the speed limits. The data were analysed using statistical anaysis on univariate and bivariate analysis. Results from univariate analysis on descriptive frequency showed that the 85"* percentile speed of car, taxi and bus almost over with the speed limits compared with motorcycle, light van and utility, medium and heavy lorry. Also the percentage of non-compliance with speed limits for car, taxi and bus were higher than motorcycle, light van and utility, medium and heavy lorry. While, from bivariate analysis the results shows eight variables were significantly associated with compliance of speed limits. They were vehicle classification, travel direction, different posted speed limits, 110 km/h posted speed limits, 90 km/h posted speed limits, 80 km/h posted speed limits, car versus taxi and private vehicle versus commercial vehicle. Therefore, road safety program should be focused on car at any posted speed limits, taxi at 90 km/h posted speed limits, bus at 110 km/h posted speed limits, direction of travelling toward CBD area and speed limits on 90 km/h. It is recommended that future engineering and non-engineering road safety programs in promoting the anti-speeding behavior through educating the public to travel with safe speed regarding with speed limit. Besides, there should be to carry out speed trapped and patrol operation on target group by the authority. Also, there is need some warn nf a nrwihte withdrawal the license permit upon any commercial vehicle those are frequently involved in violation of speed limit. Last but not least, by enforcing on commercial vehicles to install with special devices on speed pedal to restricted form speeding over speed limits.